Probing on the Relationship between Students' Self-Confidence and Self-Efficacy while engaging in Online Learning amidst COVID-19 - Quiana Althea Blanco; Mark Lyster Carlota; Ashley Janine Nasibog; Beatriz Rodriguez; Xydel Vie Saldaña; Elaisha Carmel Vasquez; Flordeliza Gagani (Journal La Edusci, 2020)
The onslaught of the Coronavirus-19 disease around the world has shaken the physical and mental well-being of the global citizenry. The student populace in particular faces added burdens and struggles in light of the pandemic due to the abrupt shift in learning modality and educational delivery to cope with the "new normal." Hence, this study aims to probe the relationship between self-confidence and self-efficacy among the randomly selected sixty (60) Grade 12 students of the University of San Carlos, Cebu City, Philippines while engaging themselves in online learning amidst COVID-19 through a descriptive correlational study. Data were gathered online using valid and reliable 4-point adapted Likert-type survey questionnaires. Results revealed that both self-confidence (x ̅= 2.61, SD= 0.84), and self-efficacy (x = 2.83, SD= 0.80) were described as high. Pearson's r correlation was also found to be significant, r (58) = .2144, p = .000059, p<0.05, which led to the rejection of the null hypothesis and led to the conclusion with at least 95% confidence that there is a moderately high positive correlation (r=0.50) between the levels of self-confidence and self-efficacy among the students while engaging in online learning. It is recommended that schools should instill policies to augment students' self-confidence and self-efficacy levels to guarantee optimal learning outcomes despite the current setting. It is also recommended that future researchers explore the same variables in public schools and far-flung areas to discover the conditional differences amidst the similarity of the shared experiences during the pandemic time.